Manajemen Perpustakaan Sekolah di SMP Negeri 1 Bojong : Tantangan dalam Menghadapi Transformasi Digital - Naila Nur Eliza; Rizki Maulida Septiani; Arinzy Rizqina; Nailatul Mafazah; Diah Puspitaningrum (Yayasan Literasi Sains Indonesia, 2026)
School libraries play a vital role in supporting the learning process and improving students' reading skills. However, library management at SMP Negeri 1 Bojong is still manual, resulting in ineffective and inefficient administrative services. Limited facilities, limited book collections, and the lack of a digital system contribute to low student reading interest. Therefore, digital transformation is needed to improve the quality of school library services. This study used a qualitative descriptive method to describe the current manual-based library management at SMP Negeri 1 Bojong. Data were collected through observation, interviews, and documentation with the head librarian, staff, and relevant teachers. The results indicate that the SMP Negeri 1 Bojong library is still manually managed, resulting in ineffective administration, services, and collection data collection. Limited professional staff, facilities, and book collections also contribute to low student reading interest. However, the library has recognized the importance of digital transformation to improve service quality, management efficiency, and student literacy development. This research shows that the library at SMP Negeri 1 Bojong is still manually managed, with limited professional staff, administrative systems, facilities, and book collections. This situation results in suboptimal library services, resulting in low student reading interest. Therefore, digital transformation is a crucial step to improve management effectiveness, service quality, and student literacy development at the school.